2008
DOI: 10.1111/j.1365-2966.2008.13207.x
|View full text |Cite
|
Sign up to set email alerts
|

On an excitation mechanism for trapped inertial waves in discs around black holes

Abstract: According to one model, high‐frequency quasi‐periodic oscillations (QPOs) can be identified with inertial waves, trapped in the inner regions of accretion discs around black holes due to relativistic effects. In order to be detected, their amplitudes need to reach large enough values via some excitation mechanism. We work out in detail a non‐linear coupling mechanism suggested by Kato, in which a global warping or eccentricity of the disc has a fundamental role. These large‐scale deformations combine with trap… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
74
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(86 citation statements)
references
References 42 publications
(65 reference statements)
9
74
3
Order By: Relevance
“…We have also tested how sensitive the results are to the magnitude of the artificial viscosity. The potential for unphysical numerical dissipation requires particularly careful consideration for the case of perpendicular kicks, since in this case the initial perturbation is an m = 0 warp that gives rise to a wave (Lubow & Pringle 1993; Ferreira & Ogilvie 2008). How such a wave physically dissipates is not obvious.…”
Section: Numerical Resultsmentioning
confidence: 99%
“…We have also tested how sensitive the results are to the magnitude of the artificial viscosity. The potential for unphysical numerical dissipation requires particularly careful consideration for the case of perpendicular kicks, since in this case the initial perturbation is an m = 0 warp that gives rise to a wave (Lubow & Pringle 1993; Ferreira & Ogilvie 2008). How such a wave physically dissipates is not obvious.…”
Section: Numerical Resultsmentioning
confidence: 99%
“…Bachev 1999; Cadez et al 2003; Wu, Chen & Yuan 2010), etc. Ferreira & Ogilvie (2008, 2009) proposed that shear velocities induced by the disc twist (see below) provide a mechanism of excitation of high‐frequency quasi‐periodic oscillations observed in many astronomical objects. Light curves, forms of emission lines of precessing twisted tori around a Kerr black hole as well as their shapes as seen from large distances have recently been investigated numerically by Dexter & Fragile (2011).…”
Section: Introductionmentioning
confidence: 99%
“…1 of Fu & Lai 2009): The so‐called p‐modes (also called inertial‐acoustic modes) have zero node in their wavefunctions along the vertical direction, while the g‐modes (also known as inertial modes or inertial‐gravity modes) 1 have at least one vertical nodes 2 . Discoseismic g‐modes have received wide theoretical attentions because they can be trapped by the GR effect without relying on special inner disc boundary conditions (Okazaki et al 1987), and they may be resonantly excited by global disc deformations (warp and eccentricity) through non‐linear effects (Kato 2003b, 2008; Ferreira & Ogilvie 2008). Kato (2003a) and Li, Goodman & Narayan (2003) (see also Zhang & Lai 2006; Latter & Balbus 2009) showed that the non‐axisymmetric g‐mode that contains a corotation resonance (CR; where the wave pattern frequency ω/ m equals the background rotation rate Ω; here ω is the mode frequency and m is the azimuthal mode number) in the wave zone is heavily damped (see Tsang & Lai 2009a for a similar study for the c‐modes).…”
Section: Introductionmentioning
confidence: 99%